Genetic predictors of attempted suicide among South Indian adolescents and young adults: A case-control study - Anju Mathew; Ann Mary Alex; Chathathayil Mohammedali Shafeeque; Saboora Beegum Muthubeevi; Vijayakumar Krishnapillai; Moinak Banerjee (Biomarkers in Neuropsychiatry)
Background: Suicide among adolescents and young adults is an alarming public health issue globally. Though studies suggest the link between genetic factors and suicidal behavior, there is a paucity of studies of specific genetic variants in adolescents and young adults. Hence this study explored the genetic predictors for attempted suicide among adolescents and young adults, by studying the genetic basis of serotonin and dopamine synthesis, transport, and degradation machinery. Methods: A Case-control association study was conducted comprising individuals with attempted suicide (cases n = 80), 13–29 years of age, belonging to Malayalam speaking Dravidian population, and attending a tertiary care center in South India. Age, sex, and ethnicity matched controls (n = 267) with no history of attempted suicide were also considered from the same ethnic population. Genotyping was performed for functionally critical SNP in serotonin receptor, Tryptophan hydroxylase, Tyrosine hydroxylase, and Catechol-o-methyl transferase. Statistical significance for allelic and genotypic comparisons and their odds ratios were computed. Results: The Tyrosine Hydroxylase THrs2070762 and Tryptophan Hydroxylase TPH1rs211105 genetic variants showed a statistically significant association with attempted suicide phenotype. Conclusion: The study suggests that the genetic variants in Tyrosine Hydroxylase and Tryptophan Hydroxylase are predictive of attempted suicide among adolescents and young adults. Understanding the genetic variations will help in identifying and managing high-risk individuals.